Peningkatan Literasi Keuangan bagi UMKM di Kabupaten Pesawaran untuk Mewujudkan Kemandirian Ekonomi (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity was carried out with the primary objective of improving the financial literacy of Micro, Small, and Medium Enterprises (MSMEs) in Pesawaran Regency. Financial literacy is considered a fundamental aspect in maintaining business continuity, as it is directly related to the ability of business actors to manage income, record transactions regularly, develop short-term and long-term financial plans, and utilize digital technology as a supporting tool. Low financial literacy is often an obstacle to the development of MSMEs, so interventions in the form of structured training and mentoring are essential. The activity method includes several stages, namely a pre-test to measure initial conditions, interactive delivery of training materials, direct practice using digital financial applications, and a post-test to disseminate learning outcomes. The evaluation results showed a significant increase in all measured indicators. Basic financial literacy increased by 10.16 points, financial recording skills increased by 14.47 points, the ability to prepare financial plans increased by 12.43 points, while financial digitalization experienced the highest performance with an increase of 18.12 points. These findings confirm that financial literacy training programs not only improve conceptual knowledge but also develop the practical skills essential for MSMEs to face the challenges of the modern economic era. This increased understanding and skills are expected to make Pesawaran MSMEs more independent, adaptable to digital technology developments, and more competitive.